Impact of Meditation–Based Lifestyle Modification on HRV in Outpatients With Mild to Moderate Depression: An Exploratory Study - Bringmann, Holger C.; Bogdanski, Martin; Seifert, Georg; Voss, Andreas (Frontiers in Psychiatry, 2022)
Background: The scientific evaluation of mind-body-interventions (MBI), including yoga and meditation, has increased significantly in recent decades. However, evidence of MBI’s efficacy on biological parameters is still insufficient. Objectives: In this study, we used HRV analysis to evaluate a novel MBI as a treatment of outpatients with mild to moderate depressive disorder. The Meditation-Based Lifestyle Modification (MBLM) program incorporates all major elements of classical yoga, including ethical principles of yoga philosophy, breathing exercises, postural yoga and meditation. Methods: As part of a larger randomized controlled trial, we compared the changes in HRV indices of a MBLM group (N=22) with those of a minimal treatment group (MINIMAL, drugs only, N=17) and a multimodal treatment-as-usual group (TAU, according to best clinical practice, N=22). Electrocardiogram (ECG) recordings were derived from a Holter monitoring device, and HRV indices have been extracted from nearly stationary 20-minute periods. Results: Short-term HRV analysis revealed statistically significant differences in the pre-to-post changes between MBLM and TAU. In particular, the vagal tone mediating RMSSD and the Rényi entropy of symbolic dynamics indicated HRV gains in MBLM participants compared with TAU. Almost no alterations were observed in the MINIMAL group. Conclusions: Our results suggest a benefit in HRV parameters for outpatients with mild to moderate depression participating in the MBLM program. For further investigations, we propose analysis of complete 24-h HRV recordings and additional continuous pulse wave or blood pressure analysis to assess long-term modulations and cardiovascular effects.